2008
DOI: 10.1103/physrevb.78.033201
|View full text |Cite
|
Sign up to set email alerts
|

Helicity asymmetry of optically pumped NMR spectra in GaAs

Abstract: The origin of σ± asymmetries in the optically-pumped NMR signal and hyperfine shift in GaAs is derived analytically and tested experimentally. The ratio of the optically-pumped to the equilibrium electron polarizations is a key parameter in determining both asymmetries. Variations in asymmetry with photon energy and laser power reflect variations in the local temperature and the electron spin polarization, and these two quantities are extracted from the asymmetry through a simple methodology. Other contributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…As pointed out in Ref. 16, if there is no helicity dependence to the diffusion constant D, the electron's lifetime τ , or J z eq , the frequency shifts observed with the two different helicities ∆ν σ± , can be used to determine the electron's polarization. It is clear, however, for Fe-doped InP, the assumptions of helicity independence for the above quantities are not correct.…”
Section: Hyperfine Shiftmentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out in Ref. 16, if there is no helicity dependence to the diffusion constant D, the electron's lifetime τ , or J z eq , the frequency shifts observed with the two different helicities ∆ν σ± , can be used to determine the electron's polarization. It is clear, however, for Fe-doped InP, the assumptions of helicity independence for the above quantities are not correct.…”
Section: Hyperfine Shiftmentioning
confidence: 99%
“…A number of authors have remarked on the hyperfine contact shift observed in some semiconductors during light irradiation [13][14][15][16] , particularly as the shift is proportional to the electron's polarization. Coles used this shift to make an absolute measurement of electron polarization in GaAs 16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An upper limit is placed on J z by J 0 , usually taken to be ±0.25 depending on light helicity 22 , although recent calculations suggest that significant deviation from this value is possible.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…22 Any dependence of these relaxation times on the normalized distance, d † = d/d 0 , from the surface, will be determined by the relaxation mechanism, as discussed below. The variable d 0 is the optical absorption depth and is photon energy dependent.…”
mentioning
confidence: 99%